Accurate wavenumber and intensity calibration for standardization of Raman spectroscopy - Raj, Ankit (2020)
Accurate wavenumber and intensity calibration are requisite for the standardization of spectroscopic techniques. Infrared spectroscopy ensures high wavenumber accuracy due to Fourier-transform spectrometers and accurate intensity scale in the unit of absorbance. Raman spectroscopy still needs improvements in wavenumber and intensity accuracies and better methods for calibration of Raman spectrometers are needed. Accurately calibrated Raman spectrometers are useful for experiments on the determination of absolute Raman cross-sections and quantitative Raman spectroscopy.